The Influence of Leadership and Motivation on Teacher’s Performance - Saputra, Hendrawan Adi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The goal of this study was to determine how teacher’s work motivation and principal’s leadership affected teacher’s performance at Tanjung Lubuk 1 Public High School. The teachers at Tanjung Lubuk 1 Public High School were the subject of this investigation. All of the teachers at SMA Negeri 1 Tanjung Lubuk served as samples in the saturated sampling technique, which uses the entire population as a sample. Distribution of questionnaires with a 5-point Likert scale measuring 75 statement items was used to collect the data. Multiple linear regression analysis is the method utilized for analysis. The findings revealed that motivation had a partial and considerable impact on teacher’s achievement, whereas leadership had a partial and minor impact. Third, that teacher motivation and the principal’s leadership both have an impact on and are important for student accomplishment.